Vertical migrations of fish schools determine overlap with a mobile tidal stream marine renewable energy device. Issue 4 (26th February 2020) - Whitton, Timothy A.; Jackson, Suzanna E.; Hiddink, Jan G.; Scoulding, Ben; Bowers, David; Powell, Ben; D'Urban Jackson, Tim; Gimenez, Luis; Davies, Alan G.
Abstract: Large increases in the generation of electricity using marine renewable energy (MRE) are planned, and assessment of the environmental impacts of novel MRE devices, such as kites, are urgently needed. A first step in this assessment is to quantify overlap in space and time between MRE devices and prey species of top predators such as small pelagic fish. Here, we quantify how the distribution of fish schools overlaps with the operational depth (20–60 m) and tidal current speeds (≥1.2–2.4 m/s) used by tidal kites, and the physical processes driving overlap. Fish schools undertake diel vertical migrations driven by the depth of light penetration into the water column, controlled by the supply of solar radiation and water column light absorption and scattering, which in turn depends on the cross‐sectional area of suspended particulate matter (SPM). Fish schools were found shallower in the morning and evening and deeper in the middle of the day when solar radiation is greatest, with the deepest depths reached during predictable bimonthly periods of lower current speeds and lower cross‐sectional area of SPM. Potential kite operations overlap with fish schools for a mean of 5% of the time that schools are present (maximum for a day is 36%). This represents a mean of 6% of the potential kite operating time (maximum for a day is 44%). These were both highest during a new moon spring tide and transitions between neap and spring tides. Synthesis and applications . Overlap of fish school depth distribution with tidal kite operation is reasonably predictable, and so the timing of operations could be adapted to avoid potential negative interactions. If all interaction between fish schools was to be avoided, the loss of operational time for tidal kites would be 6%. This information could also be used in planning the operating depths of marine renewable energy (MRE) devices to avoid or minimize overlap with fish schools and their predators by developers, and for environmental licencing and management authorities to gauge potential ecological impacts of different MRE device designs and operating characteristics. Abstract : Overlap of fish school depth distribution with tidal kite operation is reasonably predictable, and so the timing of operations could be adapted to avoid potential negative interactions. If all interaction between fish schools was to be avoided, the loss of operational time for tidal kites would be 6%. This information could also be used in planning the operating depths of marine renewable energy (MRE) devices to avoid or minimize overlap with fish schools and their predators by developers, and for environmental licencing and management authorities to gauge potential ecological impacts of different MRE device designs and operating characteristics. Crynodeb: Mae'n fwriad cynhyrchu llawer mwy o drydan yn defnyddio ynni adnewyddadwy'r môr, ac mae angen ar frys i asesu effeithiau amgylcheddol dyfeisiau newydd ynni adnewyddadwy'r môr, megis barcutiaid. Cam cyntaf yr asesiad hwn yw meintioli'r gorgyffwrdd sydd o ran amser a lle rhwng dyfeisiau ynni adnewyddadwy'r môr a'r rhywogaethau y mae'r ysglyfaethwyr pennaf yn eu bwyta megis pysgod pelagig bach. I wneud hyn rydym yn meintioli sut mae dosbarthiad heigiau pysgod yn gorgyffwrdd â'r dyfnder gweithredol (20–60 m) a chyflymder cerrynt y llanw (≥1.2–2.4 m/s) lle gellir defnyddio barcutiaid llanw ynghyd â'r prosesau ffisegol sydd wrth wraidd y gorgyffwrdd. Mae heigiau pysgod yn ymgymryd â mudo fertigol dyddiol mewn ymateb i ddyfnder treiddiad golau i'r golofn ddŵr. Yr hyn sy'n rheoli hynny yw'r cyflenwad ymbelydredd solar ac amsugnedd a gwasgariad golau yn y golofn ddŵr, sydd yn ei dro yn dibynnu ar arwynebedd trawstoriadol gronynnau (SPM) yn y dŵr. Canfuwyd heigiau pysgod mewn dŵr basach yn y bore a gyda'r nos ac mewn dŵr dyfnach ganol dydd pan fo ymbelydredd solar ar ei gryfaf, a chyrhaeddwyd y dyfnderoedd mwyaf yn ystod y cyfnodau deufisol y mae modd eu rhagweld pan fo cyflymder y cerrynt yn arafach a nifer y gronynnau yn y dŵr yn llai. Mae'r cyfleoedd posib ar gyfer defnyddio barcutiaid yn gorgyffwrdd â heigiau pysgod tua 5% o'r amser, o ran cymedr, pan fo'r heigiau'n bresennol (uchafswm diwrnod yw 36%). Mae hyn yn cynrychioli cymedr o 6% o amser gweithredu posib y barcutiaid (uchafswm diwrnod yw 44%). Roedd y rhain ar eu huchaf ar lanw mawr lleuad newydd ac yn y cyfnod rhwng llanw bach a llanw mawr. Synthesis a chymwysiadau . Mae'n rhesymol rhagweld bod gorgyffwrdd rhwng dosbarthiad dyfnder heigiau pysgod â gweithrediad barcutiaid llanw, ac felly gellid addasu pryd y cânt eu gweithredu er mwyn osgoi rhyngweithio negyddol posibl rhwng y ddau beth. Pe llwyddid i osgoi unrhyw ryngweithio â heigiau pysgod, 6% o amser gweithredol y barcutiaid llanw fyddai'n cael ei golli. Gellid defnyddio'r wybodaeth hon hefyd wrth gynllunio dyfnderoedd gweithredu dyfeisiau ynni adnewyddadwy'r môr er mwyn osgoi neu leihau'r achosion pan fo datblygwyr yn gorgyffwrdd â heigiau pysgod, a gallai awdurdodau trwyddedu a rheoli amgylcheddol ei defnyddio i fesur effeithiau ecolegol a nodweddion gweithredu gwahanol ddyfeisiau ynni adnewyddadwy'r môr.